KOMPENSASI PERANGKAT DESA DI DESA ADIMULYA KECAMATAN WANAREJA - Hasan Muzaki (AmaNU: Jurnal Manajemen dan Ekonomi, 2023)
This research is entitled Compensation for Village Officials in Adimulya Wanareja Village. From the results of the author's observations and research, it can be concluded that the compensation for the Adimulya Village apparatus, seen from the perspective of the amount obtained, still needs to be increased, as well as the event and time of administration. It is hoped that this will become the government's attention to pay more attention to the welfare of village officials.